Measurement of Social Media Marketing Performance on Klik-Amazing’s Product At Marketing Division, Klik-Amazing - Alim, Ihwanul; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2012)
Internet in Indonesia grew fast. Indonesian do socialize in online social media, also. Klik-Amazing was small company run in media industry and used online social media to do the marketing communication.Customer’s media habit consumption also shifting from offline media (without internet) into offline and online (by internet) media, including the online social media. The most used online social media were facebook and twitter. Klik-Amazing prepares their low cost-marketing strategy by these online social media. With online social media, Klik-Amazing measured the market’s response on applied marketing strategy.This online marketing measured by Klout, an influence measurement tool on social media internet and facebook fan page analytics, which analyze brand/company’s influence in facebook. The results compared with online target that had been decided before by Klik-Amazing.Facebook fan page utilization on 2 months produce 57 fans, photo as most influence medium, 96,60% of fans and 84.80% reached people were appropriate with target market’s identitiy. The sales of company grew into 1,600,000/month in 5 months. The klout score increase into 32 with ‘Conversationalist’ as the klout style. Those results had achieved the online targets and considered success.By this final project, AISAS model had been modified into the model that optimizes the utilization of facebook, twitter and website. Besides, another model had been hypothesized to simulate how Klout can generate the Klout-Score and Klout-Style in increasing the online influence in social media. These two models were not proved yet and recommended to be researched further. Keywords: Klik-Amazing, Social Media Strategy, AISAS Model